Investigating The Role of Emotional Intelligence in The Relationship Between Adversity Quotient and Self Efficacy To Work Stress - Aulia Aulia; Mochamad Sofwan; Intan Apriadi; Priyono Priyono; Mochamad Soelton (Universitas Mercu Buana, 2023)
Human resources is very important for companies in managing, regulating, and empowering employees so that they can function productively to achieve company goals. Human resources in the company need to be managed professionally in order to realize a balance between the needs of employees and the demands and capabilities of the company's organization. Employees are placed according to their skills and abilities, high level of company work, high work motivation, high work participation, effective work communication, high work discipline, employee wages and salaries are determined fairly according to position, education, and responsibilities tall one. The purpose of this study was to analyze the role of Adversity Quotient and Self Efficacy on Job Stress mediated by Emotional Intelligence at PT. Tripuri Mitra Nobelindo. Using a saturated sample with a total of 50 employees, the analysis was carried out quantitatively with the method of collecting questionnaires. Structural Equation Model (SEM) was used as an analytical method and Smart – PLS was used as an analytical tool. The results of the study, Adversity Quotient has a significant negative effect on Job Stress, Self efficacy has a significant negative effect on Job Stress, Adversity Quotient has a significant positive effect on Emotional Intelligence, Self Efficacy has a significant positive effect on Emotional Intelligence, Emotional Intelligence has a significant negative effect on Job Stress, Adversity Quotient does not have a significant effect on Job Stress through Emotional Intelligence, and Self Efficacy has a significant negative effect on Job Stress through Emotional Intelligence.